The Impact of Monetary Policy on Inflation - Ramlan, Hamidah (International Journal of Psychosocial Rehabilitation, 2020)
the objective of this study is to scrutinize an association between inflation, consumption and saving in Malaysia. The Data was collected and retrieved from www.bursamalaysia.com, Bank Negara and Statistic Department cover from period of 1990 to 2018. Throughout, this study uses multiple linear regressions to run the dependent variable saving with its independent variables. The result shows a statistically significant relationship between the inflation, consumption and saving.